Pengaruh Aplikasi Perlakuan Manajemen Pupuk Organik Terhadap Pertumbuhan Dan Serapan Hara NPK Tiga Varietas Padi Gogo - Burhan, Moh Shohibul; Nurhidayati; Basit, Abdul (Folium : Jurnal Ilmu Pertanian, 2024)
The extensive use of inorganic fertilizer can affect soil fertility. To overcome these problems it is necessary to improve soil fertility. One of them is by adding organic matter using organic fertilizer. The purpose of this study was to determine the effect of the application of organic fertilizer management on growth and NPK nutrient uptake of three varieties of upland rice. his experiment used a factorial randomized block design. The first factor was a variety consisting of three levels, namely: V1 (Inpago 8), V2 (Inpago 12), and V3 (Inpago 13 Fortiz). The second factor was a organic fertilizer management which consists of four levels, namely: F1 (recommended dose of inorganic fertilizer), F2 (cow dung + biochar), F3 (solid vermicompost + biochar) and F4 (nanovermicompost + biochar). The research results showed that in general the V1F1 treatment (Inpago 8 with recommended doses of inorganic fertilizer) gave a good response to the growth of upland rice. Kinds of organic fertilizer management treatment using vermicompost is the best treatment